PERAN ETNOMATEMATIKA DALAM PEMBELAJARAN MATEMATIKA PADA KURIKULUM 2013 - Melkior Wewe; Heldiana Kori Yusman (Lembaga PKBM Tunas Harapan Varoso, 2025)
This study aims to describe the function of ethnomathematics in learning mathematics in the 2013 curriculum. This research uses library research, observation and documentation as its methods. Secondary data is information that has been collected and examined from various sources including research reports, books, journals, websites, and other related materials and pays attention to accurately data regarding ethnomathematics in learning mathematics. The three stages of data analysis used in this research are organization, synthesis, and identification. (1) Ethnomathematics helps the preservation and continuation of cultural traditions in mathematics education, according to research findings. (2) Because ethnomathematics is related to the notion of mathematics in society, it can be taught along with traditional mathematics. (3) Because it allows students' experiences as members of cultural communities to have contextual meaning, ethnomathematics in culture-based mathematics learning will be an interesting, entertaining, and novel learning approach.